Multiliteracias e multimodalidade no ensino de português na UNTL - Faria, Paulo M.; Soares, Susana (Linguarum Arena, 2020)
Within the scope of the FOCO.UNTL Project, whose mission is to contribute to improve the quality of teaching in Timor-Leste and to consolidate the Portuguese language as an instrument for acquiring and accessing knowledge, this article aims to discuss and present innovative learning scenarios for the development of a multiliteracy and multimodal approach to language teaching. Given the infrastructural, material and human limitations, the smartphone was used as a privileged resource in several tasks developed in the didactic sequences of a 1st year course. As for the methodology, it was decided to carry out a study that privileges a qualitative approach, although statistical results are obtained from the data collected through a questionnaire and the logbook. The data collection instruments made it possible to identify i) the group’s biographical and socioeconomic characteristics; ii) access to and use of digital media; iii) the activities for which the cell phone was used in the classroom and iv) the perception of these activities in terms of advantages and disadvantages. From this article, which constitutes the first phase of a broader study of this matter, it can be concluded that, although the use of digital media places additional demands on teaching, this is a path of no return. Therefore, the need to develop new skills in discourse analysis in students, to the point of enabling them to represent the world in different semiotic ways, must be a central point in the organization and dynamization of pedagogical activities.